Studying the effected of replacing wheat flour with barley flour on the physicochemical, sensory and taste properties of petit fours (Journal of Hama University, 2025)
Abstract:The aim of the research was to study the effect of the proportions of substitution of standardized wheat flour used in the manufacture of petit fours with white barley flour at three levels of 30-20-10% on the physicochemical, sensory and taste properties of petit fours. Standardized wheat flour with an extraction rate of 80% (food flour) and samples of white barley flour with an extraction rate of 80% were used. This research was conducted in the Grain Technology Laboratory, Department of Food Sciences, Faculty of Agricultural Engineering, Deir Ezzor, during the years 2023-2024.The results showed an increase in the percentage of proteins, moisture, ash and crude fibers with increasing substitution ratios of 30-20-10%. A significant decrease was also observed in the percentage of wet gluten for the mixtures prepared from flour with different substitution ratios with barley flour with increasing substitution ratios. The sensory and taste properties of
Keywords: petit fours, barley flour, wheat flour, physicochemical properties